Beyond the Information Technology Agreement: Harmonisation of Standards and Trade in Electronics - Portugal-Perez, Alberto (2012)
Product standards can have a dual impact on costs and, thus, on trade. They can impose costs on exporters as it may be necessary to adapt products for specific markets (cost effect). In contrast, standards can reduce exporters' information costs as they convey information on product characteristics (informational effect). Using a new World Bank database of European standards for electronic products, we examine the net impact of internationally harmonised European standards on European Union imports. We find that European Union standards for electronic products that are harmonised to international standards have a significant and a positive net effect on trade. The results suggest that efforts to promote trade in electronic products could be complemented by steps to promote standards harmonisation. This might include, for example, restarting talks to extend the WTO's Information Technology Agreement to commitments to harmonise national standards in electronic products.